A comparative review on privacy concerns and safety demands of closed-circuit television among Taiwan, Japan, and the United Kingdom. Issue 1 (2nd January 2017) - Wu, Yu-Lung; Tao, Yu-Hui; Chang, Chi-Jui
Abstract: Closed-circuit television (CCTV) surveillance can be used to effectively prevent crime and enable people to feel safe, but most countries tend to emphasize safety over privacy. This study proposed an analysis framework for comparing CCTV legislation and privacy protection among Taiwan, the United Kingdom (UK), and Japan in an attempt to reverse the phenomenon of safety outweighing privacy. The UK and Japan have the richest CCTV studies worldwide and in Asia, respectively. In contrast, Taiwan has dense installation but few CCTV studies. Furthermore, the local CCTV studies in Japan and Taiwan are unfamiliar to the West. Comparison results indicated that the largest disparities in CCTV policy were related to dissimilar regulations and cultures, but the three countries consistently adhered to the principle of protecting public privacy. Based on the comparison, the study referenced relevant research to discuss the CCTV legislation among the three countries and propose practical and research recommendations.